Pengaruh Kombinasi Terapi Foot Massage dan Murottal Alquran terhadap Tingkat Kelelahan Pasien yang Menjalani Hemodialisa - Fatkhal Khairu Najib; Erna Rochmawati; Akhmad Zuhri (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Chronic kidney failure occurs due to a decrease in kidney function, causing an imbalance in the body's metabolism, fluids and electrolytes which can result in uremia. Patients with chronic renal failure must undergo routine hemodialysis therapy. Hemodialysis therapy can cause nursing problems, namely fatigue. Fatigue can be caused by a lack of hemoglobin levels in patients or the length of the hemodialysis process. The research method used in this research is a case report by evaluating the implementation of a combination intervention of foot massage and murottal therapy Surat Ar Rahman. The instrument for measuring fatigue levels uses the FACIT-fatigue scale questionnaire. The results of this study showed that the patient experienced high fatigue with a score of 10.5 and after being given a combination of relaxation intervention of foot massage and murottal Al-Quran therapy, the patient's fatigue level score became 18.2 or moderate fatigue. From these results, it can be concluded that there is an effect of providing a combination of relaxing foot massage and murottal therapy on reducing the level of fatigue in chronic kidney failure patients undergoing hemodialysis.